Do Field-Free Electromagnetic Potentials Play a Role in Biology? - Szasz, A.; Vincze, G.; Andocs, G.; Szasz, O. (Electromagnetic biology and medicine, 2009)
All bio-systems are imperfect dielectrics. Their general properties however cannot be described by conventional simple electrodynamics; the system is more complex. A central question in our present paper is centered on a controversial debate of the possible effect of the zero fields (only potentials exist). We show that the identical use of the "field-free," "curl-free," and "force-free" terminologies is incorrect, there have definitely different meanings. It is shown that the effective electro-dynamical parameters that describe and modify living systems are the potentials and not the fields. We discuss how the potentials have a role in biological processes even in field-free cases.